The Mediating Role of Self-Exertion on the Effects of Effort on Learning Virtues and Emotional Distress in Academic Failure in a Confucian Context - Fwu, Bih-Jen; Chen, Shun-Wen; Wei, Chih-Fen; Wang, Hsiou-Huai (Frontiers in Psychology, 2017)
Previous studies have found that in East Asian Confucian societies, hardworking students are often trapped in a dilemma of enjoying a positive moral image while suffering from emotional distress due to academic failure. This study intends to further explore whether the cultural-specific belief in self-exertion acts as a psychological mechanism to lessen these students’ negative emotions. A group of 288 college students in Taiwan were administered a questionnaire to record their responses to past academic failures. The results from structural equation modeling showed that self-exertion functioned as a mediator between the effects of effort on learning virtues and emotional distress. Self-exertion to fulfill one’s duty to oneself positively mediated the effect of effort on learning virtues, whereas self-exertion to fulfill one’s duty to one’s parents negatively mediated the effect of effort on emotional distress. Theoretical and cultural implications are further discussed.